Dwa zebra Adama . Adam's Two Ribs - Morgenstern, Janusz (Syrena, 1964)
Duration: 01:22:00 An engineer comes back to his home town after a long stay abroad. His wife soon discovers that he married another woman there, and they decide to start living together. The conservative local community cannot bear it, especially as the trio seems to be getting on well. Local party officials, the local priest and even the public prosecutor want to have their say. Only the engineer cannot decide who to stay with, as he does not want to hurt either of the women. A satirical comedy of manners portraying a small-town Poland where everybody knows everything about everyone.